Uptake by COPI-coated vesicles of both anterograde and retrograde cargo is inhibited by GTPγS in vitro - Nickel, Walter; Malsam, Jörg; Gorgas, Karin; Ravazzola, Mariella; Jenne, Nicole; Helms, J. Bernd; Wieland, Felix T. (Journal of cell science, 1998)
On the basis of the cell surface protein CD8 we have constructed reporter molecules for both anterograde and retrograde transport from the Golgi complex. The cytoplasmic tail of CD8 was exchanged by a construct comprising a hemagglutinin (HA) epitope, the C-terminal sequence of the viral protein E19 (containing a KKXX retrieval signal) followed by a myc epitope (CD8-LT). Due to this masking of the KKXX retrieval signal CD8-LT is transported to the cell surface. Since the KKXX motif is joined to the myc epitope via a thrombin cleavage site, CD8-LT in isolated Golgi membranes can be proteolytically converted into an unmasked reporter molecule for retrograde transport (CD8-ST) in vitro. A CHO cell line stably expressing CD8-LT was generated and used for the isolation of Golgi membranes. These membranes were shown to contain CD8-LT en route to the cell surface. By addition of thrombin, CD8-LT could be efficiently converted into CD8-ST, and this allows us to study the sorting into coat protein COPI-coated vesicles of these different kinds of cargo on a comparative basis. COPI-coated vesicles were generated in vitro from Golgi membranes containing either CD8-LT or CD8-ST. When the incubation was performed in the presence of GTP, both CD8-LT and CD8-ST were packaged into COPI-coated vesicles. However, COPI-coated vesicles generated in the presence of the slowly hydrolyzable analogue of GTP, GTPγS contained strikingly lower amounts of CD8-LT and CD8-ST. While COPI-coated vesicles accumulated about 12-fold in the presence of GTPγS these vesicles together contained only one fifth of cargo compared to the few vesicles generated in the absence of GTPγS. These data indicate that cargo packaging into COPI-coated vesicles requires hydrolysis of GTP.
Gesehen am 22.04.2025